Matrix metalloproteinase‐12 is associated with overall survival in Chinese patients with gastric cancer1. Issue 7 (27th December 2012) - Zheng, Jianyong; Chu, Dake; Wang, Desheng; Zhu, Yongsheng; Zhang, Xiaoyin; Ji, Gang; Zhao, Haihong; Wu, Guosheng; Du, Jianjun; Zhao, Qingchuan
Abstract Background and Objectives Matrix metalloproteinase‐12 (MMP‐12) plays an important role in invasion and metastasis of human solid tumor cells. This study aimed to investigate the association of MMP‐12 with overall survival in human gastric cancer. Methods Gastric cancer and adjacent normal tissue specimens were collected from 165 patients who had not received neoadjuvant chemotherapy. MMP‐12 expression was determined by immunohistochemical staining, and the results were analyzed statistically in relation to the overall survival of the patients. Results MMP‐12 expression was increased in gastric cancer compared with that observed in normal tissues. Increased MMP‐12 expression was associated with tumor invasion, lymph node metastasis, distant metastasis, and TNM stage. No correlations were detected between MMP‐12 expression and age, sex, differentiation status, tumor site, or Lauren classification. Moreover, patients with MMP‐12 positive gastric cancer tended to have worse overall survival compared with those patients without MMP‐12 expression. Conclusions The study results showed that increased expression of MMP‐12 was associated with tumor progression in gastric cancer. It also provided the first evidence for MMP‐12 expression in gastric cancer as an independent prognostic factor. J. Surg. Oncol. 2013;107:746–751. © 2012 Wiley Periodicals, Inc.